A comparative study of palladium-gold and palladium-tin catalysts in the direct synthesis of H2O2 - Kovačič, D; Lewis, RJ; Crombie, CM; Morgan, DJ; Davies, TE; López-Martín, Á; Qin, T; Allen, CS; Edwards, JK; Chen, L; Skjøth-Rasmussen, MS; Liu, X; et al. (Royal Society of Chemistry, 2023)
Herein we evaluate the promotive effect of Au and Sn incorporation into supported Pd nanoparticles for the direct synthesis of H2O2 from molecular H2 and O2. The introduction of both secondary metal modifiers was found to result in a significant enhancement in catalytic performance, although, in the case of the PdSn system, it was identified that relatively large quantities of the secondary metal were required to rival the activity observed over optimal Au-containing formulations, with the 0.25%Pd-2.25%Sn/TiO2 catalyst offering comparable H2O2 synthesis rates to the optimised 0.25%Pd-0.25%Au/TiO2 formulation. The introduction of Sn was found to considerably improve Pd dispersion, correlating with an improvement in selective H2 utilisation. Notably, the optimal PdSn catalyst identified in this work achieves superior H2O2 selectivities compared to the PdAu analogue and is able to rival the performance of state-of-the-art materials.